Analysis of headache burden Chinese in the global context from 1990 to 2021 - Zhao, Wenxuan; Chen, Yonglin; Tang, Yushi; Du, Shiqing; Lu, Xiaojie (Frontiers in Neurology, 2025)
BackgroundHeadache is one of the leading causes of disability in worldwide and in China, and the second most burden disease of the nervous system after stroke. We aimed to analyze the global trends in the burden of headache disorders, migraine and TTH among people in China in an international context.MethodsData were taken from the Global Burden of Disease (GBD) Study 2021 database to examine trends in the incidence, prevalence, and disability-adjusted life year of headache disorders.ResultsIn the context of a large scale in the world, headache is currently in a state of high incidence in China, and female middle-aged and young patients are the main body of this disease.ConclusionsNeed to focus on the vulnerable population in China, while formulating effective health policies and developing good treatment measures to reduce the incidence of headache disorders and improve the DALYs rate of headache.